2010
DOI: 10.1007/s11071-010-9676-8
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study on the dynamic response of planar multibody systems with multiple clearance joints

Abstract: A general methodology for dynamic modeling and analysis of multibody systems with multiple clearance joints is presented and discussed in this paper. The joint components that constitute a real joint are modeled as colliding bodies, being their behavior influenced by geometric and physical properties of the contacting surfaces. A continuous contact force model, based on the elastic Hertz theory together with a dissipative term, is used to evaluate the intra-joint contact forces. Furthermore, the incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(134 citation statements)
references
References 61 publications
7
126
0
1
Order By: Relevance
“…Friction modelling has progressed from specific models analysing friction at the interface of geometries [11][12][13][14], to the analysis of friction at manipulator joints [4,7,15] with clearance and their kinematics and dynamic [16][17][18][19][20][21][22][23][24][25]. Marques et al [26] have recently surveyed friction models in single degree of freedom in planar systems.…”
Section: List Of Symbolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Friction modelling has progressed from specific models analysing friction at the interface of geometries [11][12][13][14], to the analysis of friction at manipulator joints [4,7,15] with clearance and their kinematics and dynamic [16][17][18][19][20][21][22][23][24][25]. Marques et al [26] have recently surveyed friction models in single degree of freedom in planar systems.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Modelling and simulation of multibody dynamics with joint clearances is relatively new area of research [96]. Three reviews are identified from literature namely Haines [101]-unlubricated revolute joints (1979), Flores (2010) [21] and Machado et al-compliant contact force models (2012) [102]. The problem of multibody impact with friction was first analysed by Routh in 1891 [100].…”
Section: Mechanistic Models With Clearance and Frictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flores et al (2004) [14] presented dynamic analysis of planar multi-body systems with revolute joint clearances, including dry contact and lubricant effect. Recently, Flores (2010) [15] presented a parametric study on the dynamic response of planar multi-body systems with multiple clearance joints. An elementary slider-crank *Address correspondence to this author at the No.2, Wen-hua West Road, Weihai, Shandong.…”
Section: Introductionmentioning
confidence: 99%